Pipeline repair by composite patch under temperature and Pressure loading (Fracture and Structural Integrity, 2019)
In this study, the three-dimensional finite element method is used to analyze an API 5L X70 steel cylindrical pipeline subjected to an internal pressure load by calculating the stress intensity factors and the integral J at the peak of crack in elastic and elastoplastic behavior. The effectiveness of composite patch repair bonded to the cracked surface is highlighted. The effects of the geometrical and mechanical properties of the composite patch and the adhesive on the effectiveness of the repair were highlighted. The variation of the stress intensity factor at the crack tip is used to evaluate the repair performance. The results obtained show that the residual heat stress significantly increases the stress intensity factor at the bottom of the crack, which reduces the effectiveness of the repair.
Keywords: FEM; Repair by composite patch; Pipeline; Cracking; Thermal stress; Internal pressure; Temperature; Stress intensity factor